1997
DOI: 10.1359/jbmr.1997.12.4.663
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Grading of Spinal Osteoporosis: Quality of Life Components and Spinal Deformity in Women with Chronic Low Back Pain and Women with Vertebral Osteoporosis

Abstract: . Spinal X-rays were reviewed in all patients for the evidence of vertebral fractures. In osteoporotic patients, vertebral deformity was quantified by the spine deformity index (SDI) on X-rays. It was assessed whether subgroups could be identified by a combination of indices for spinal deformation (SDI, HR, DOW) using a cluster analysis. Back pain was a major complaint in both groups, without differences in pain intensity and frequency. Impairment of general well being and mood was found in about one-third of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
16

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(80 citation statements)
references
References 47 publications
1
62
0
16
Order By: Relevance
“…The analysis of the current literature is confusing as far as the most appropriate timing of application of VP and KP is concerned. On the one hand, it is suggested that VP should be considered after a course of 3 months of conservative treatment [16]. On the other, supporters of KP suggest that the procedure should be done within 3 months from fracture to increase the likelihood of a favourable outcome [10], or even within a few days from fracture to achieve a good restoration of vertebral height [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the current literature is confusing as far as the most appropriate timing of application of VP and KP is concerned. On the one hand, it is suggested that VP should be considered after a course of 3 months of conservative treatment [16]. On the other, supporters of KP suggest that the procedure should be done within 3 months from fracture to increase the likelihood of a favourable outcome [10], or even within a few days from fracture to achieve a good restoration of vertebral height [11].…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic VCFs (about 30% of all VCFs esteemed to occur in the western world) can be associated with decreased quality of life and increased mortality in the elderly [9,16]. Irrespective of fracture pain, disability associated with VCFs is apparently caused by changes in the alignment of the spine and related to the severity of spinal deformity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Half of the patients become dependent on other people᾿s help, and about one-third become completely immobile. [5,6] The number of hip fractures in the world in 1990 was 1.7 million, and it is expected that the number by 2050 will be 6.3 million as the incidence of hip fractures increases with age. Costs for hip fractures in 2002 were 48 billion dollars, and this will have a manifold increase in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the current literature is confusing as far as the most appropriate timing of application of VP and KP is concerned. On the one hand it is suggested that VP should be considered after a course of 3 months of conservative treatment 2 . On the other, supporters of KP suggest the procedure should be done within three months from fracture to increase the likelihood of a favourable outcome 16 , or even within a few days from fracture to achieve a good restoration of vertebral height 17 .…”
Section: Discussionmentioning
confidence: 99%